SPIRITUAL INTERVENTIONS TOWARDS IMPROVING PALLIATIVE CARE WELL-BEING OF BREAST CANCER PATIENTS: A SYSTEMATIC REVIEW - Fauzi, Achmad; Putri, Adelia; Setiawan, Aisyah Rachma; Dwicahyani, Karin Nur; Utami, Ajeng Rahayu; Salsabilla, Aura Rizka; Saputri, Adelia Febriana; Fauzan, Chandra Rizky; Yunianti, Aldina (HEARTY, 2026)
Breast cancer is a disease that is still a major problem in women’s health. The disease causes significant physical, emotional, and psychological impacts for sufferers. Palliative care not only focuses on physical treatment, but also includes psychosocial and spiritual aspects that affect the overall well-being of patients. In this context, spiritual intervention has been identified as an approach that can provide significant emotional and psychological support, help patients feel calmer, and accept their condition better. This study aims to synthesize a study on spiritual interventions to improve the welfare of palliative patients with breast cancer. The research method used is a systematic review through data bases, namely PubMed, ProQuest, and Google Scholar, for studies published between 2019 and 2024. The keywords used include "palliative", "spiritual" and "breast cancer". Based on the nine studies listed, the results show that spiritual interventions, such as the Spiritual Emotional Freedom Technique (SEFT), Spiritual Guided Imagery (SGI), prayer practices and faith-based approaches, have a significant impact on reducing stress, anxiety, and depression, as well as improving the quality of life and spiritual well-being of patients. These findings underscore the importance of integrating spiritual support in palliative care to help patients better cope with the challenges of the disease.